Employment protection reform in search economies - Olivier L'Haridon; Franck Malherbet (Institute for the Study of Labor (IZA), 2006)
The design of the employment protection legislation (EPL) is of a particular acuity in the European debate on the contours of the EPL reform. In this article we used an equilibrium unemployment model to investigate the virtue of an EPL reform whose modality is a lessening in the red tape and legal costs associated with layoffs and the introduction of an U.S. like experience rating system modelled as a combination of a layoff tax and a payroll subsidy. The reform considered shows that it is possible to improve both the consistency and the efficiency of employment protection policies while leaving the workers' protection untouched on the labor market. These results are consistent with the conventional wisdom that experience rating is desirable, not only as a part of unemployment compensation finance as most studies acknowledge but also as part and parcel of a virtuous EPL system
Keywords: 330; Arbeitsmarkt; Reform; Kündigungsschutz; Arbeitsplatzsuchmodell; EU-Staaten